SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KOTA TUJUAN WISATA WILAYAH JAWA BALI MENGGUNAKAN METODE AKSIDENTAL SAMPLING (STUDI KASUS DI GRAS TOUR AND TRAVEL YOGYAKARTA) - Ismi Yuniati; Anton Setiawan Honggowibowo; Yuliani Indrianingsih (Compiler, 2013)
Tourist attraction in Indonesia is one of the natural resources to be proud. That we need an alternative build Decision Support System Application. This application shows can assist determine the potential tourist travel destination, make memorable and accordance with the characteristics potential tourists addition this application saves the time and effort find a tourist destination because it can be accessed anywhere. The final result steps by steps, the best obtained from two respondents are Afriani 105 for the city o f Yogyakarta and Damar 84 for the city o f Sukabumi. Based on these results, system is able to determine built the city as desired tourist destination and tourist characteristics.